Induced abortion according to immigrants' birthplace: a population-based cohort study - Susitha Wanigaratne; Mei-ling Wiedmeyer; Hilary K. Brown; Astrid Guttmann; Marcelo L. Urquia (BMC, 2020)
Abstract Background Most abortions occur due to unintended pregnancy. Unintended pregnancies are linked to poor health outcomes. Canada receives immigrants from countries with disparate sexual and reproductive health contexts which may influence abortion rates post-migration. We examined the association between abortion and region of birth and birth order among Canadian immigrants. Methods We conducted a population-based person-years (PY) cohort study in Ontario, Canada using administrative immigration (1991-2012) and health care data (1991-2013). Associations between induced abortion and an immigrant's region of birth were estimated using poisson regression. Rate ratios were adjusted for age, landing year, education, neighborhood income quintile and refugee status and stratified by birth order within regions. Results Immigrants born in almost all world regions (N = 846,444) were 2-5 times more likely to have an induced abortion vs. those born in the US/Northern & Western Europe/Australia & New Zealand (0.92 per 100 PY, 95% CI 0.89-0.95). Caribbean (Adjusted Rate Ratio [ARR] = 4.71, 95% CI 4.55-4.87), West/Middle/East African (ARR = 3.38, 95% CI 3.26-3.50) and South American (ARR = 3.20, 95% CI 3.09-3.32) immigrants were most likely to have an abortion. Most immigrants were less likely to have an abortion after vs. prior to their 1st birth, except South Asian immigrants (RR = 1.60, 95% CI 1.54-1.66; RR = 2.23, 95% CI 2.12-2.36 for 2nd and 3rd vs 1st birth, respectively). Secondary analyses included further stratifying regional models by year, age, education, income quintile and refugee status. Conclusions Induced abortion varies considerably by both region of birth and birth order among immigrants in Ontario.